Post‐repair laxative management in obstetric anal sphincter injury guidelines: A narrative review. (12th August 2022) - Tucker, Julie; Hassam, Tayla; Juszczyk, Karolina; Briley, Annette; Parange, Anupam; Murphy, Elizabeth Mary Anne
Abstract : Background: Childbirth is a common factor which increases the risk of obstetric anal sphincter injuries (OASIS). Damage to the anal sphincters increases the risk of anal incontinence, which has a debilitating impact on the quality of life. Post‐repair laxatives are prescribed in this group of women. However, there is no consensus regarding the type or frequency with which they are used, and available guidelines lack consistency and evidence to support the recommendations. Aim: The aim was to review and compare the international, national and local Australian management guidelines for recommendations regarding laxative use in women after OASIS. Method: An online literature search of medical and nursing databases such as PubMed, Embase, MEDLINE, CINAHL, Web of Science, Scopus and Cochrane was performed between January 2000 and October 2020. Full‐text articles with MeSH headings and Text Words [TW] identified guidelines in the prevention, management and care of OASIS. The search terms included 'obstetric anal sphincter injury', 'OASIS', 'perineal tear', 'postpartum continence', 'bowel injury', 'aperient', 'laxative use' and 'bulking agents'. Results: Thirteen guidelines were included. Laxatives were recommended in most guidelines; however, there was a lack of consistency regarding the type of laxative used, frequency, dose and duration of use. Guidelines were based on historical evidence, with paucity of recently acquired data identified. Conclusions: There is no consensus regarding an optimal laxative regime for women who sustain an anal sphincter injury after childbirth. Further research is required to develop evidence‐based robust clinical guidelines regarding laxative use in women who sustain OASIS.